2019
DOI: 10.1002/ppsc.201900105
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Branched Molybdenum‐Based Bioactive Nanoparticles Significantly Promote Osteogenic Differentiation of Adipose‐Derived Stem Cells

Abstract: Adipose‐derived stem cells (ADSCs) are considered to be ideal stem cell sources for bone‐tissue regeneration owing to their ease of collection and high activity. However, the regulation of osteogenic differentiation of ADSCs using biomaterials without adding growth factors is still not satisfactory. For the first time, molybdenum‐doped bioactive glass nanoparticles with a radial porous morphology (Mo‐rBGNs) are reported and their role in the osteogenic differentiation of ADSCs is investigated. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…The enhanced osteogenic differentiation of ADMSCs was probably attributed to the bioactive feature of BGNs and GP. Previous studies showed that monodispersed BGNs could induce the osteogenic differentiation of ADMSCs through the signaling pathway of TGF‐beta 14,33. The main reasons of GP functionalization enhancing the osteogenic differentiation of BGN on ADMSCs could be shown as follows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced osteogenic differentiation of ADMSCs was probably attributed to the bioactive feature of BGNs and GP. Previous studies showed that monodispersed BGNs could induce the osteogenic differentiation of ADMSCs through the signaling pathway of TGF‐beta 14,33. The main reasons of GP functionalization enhancing the osteogenic differentiation of BGN on ADMSCs could be shown as follows.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that monodispersed bioactive glass nanoparticles (BGNs) presented enhanced cell uptake and biodegradation, and improved biominerialization ability, demonstrated promising biomedical applications in bioimaging, gene delivery, bone regeneration, and wound healing 10,21,25,27,30. Monodispersed BGNs and nanoscale silicon‐based biomaterials could also efficiently enhance the osteogenic differentiation of osteoblasts and bone marrow stem cells 31–33. Recent years, our group further found that monodispersed BGNs could induce the osteogenic differentiation of adipose mesenchymal stem cells (ADMSCs) through activating the TGF‐beta signaling pathway, and the molybdenum‐based branched BGNs could also promote the osteogenic differentiation of ADMSCs 34,35.…”
Section: Introductionmentioning
confidence: 98%
“…BGNs compared with traditional bioactive glass have a controlled surface area, which improves the local formation of apatite and osteogenic bioactivity. [ 101,212 ] Chen et al. (2020) decided to use poly(citrate‐siloxane) (PCS) to coat the surface of BGNS (BGNS@PCS) to produce photoluminescent biomimetic elastomeric BGNS with potential application in bioimaging.…”
Section: D Printing and Nanotechnology Alliancementioning
confidence: 99%
“…In addition, recent studies show the possibility of further benefit brought by these materials. They may have other advantages such as the functionalization of their surface for the transport of molecules [9] of biological interest and activates biological reactions useful for the restoration of bone tissue such as cell differentiation [10], osteogenesis and angiogenesis [11]. All these characteristics must be investigated during the engineering of new biomaterials.…”
Section: Introductionmentioning
confidence: 99%